Innovations in higher education: methodological and theoretic approaches and their practical implementation - Tarantey, Viktor P. (Journal of the Belarusian State University. Journalism, 2019)
In the article on extensive theoretical and practical material are characterized the concept’s «innovation in education» essence, the methodological and theoretical approaches in the innovative sphere of the educational process and their practical implementation in the modern higher vocational education. It is proved that methodological ideas about innovations in education (the innovative processes in professional education, innovation dynamics and new knowledge, etc.) are of particular value. Innovations in education can be made through the forms and methods of education and through innovative technologies. It is stated that pedagogical innovation can be considered a deeper and broader innovation, leading to the realization of a core innovative idea in controversy with many authors. This conclusion is argued by several examples from different authors’ scientific research.